A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28S rDNA sequences, with a key to species of the genus - Hernández-Mena, David Iván; Lynggaard, Christina; Mendoza-Garfias, Berenit; de León, Gerardo Pérez-Ponce (Zootaxa, 2016)
We describe a new species of Auriculostoma Scholz, Aguirre-Macedo & Choudhury, 2004 based on several sources of information including morphology (light and scanning electron microscopy [SEM]), sequences of two nuclear genes, host association, and geographical distribution. Morphologically, the new species most closely resembles Auriculostoma astyanace Scholz, Aguirre-Macedo & Choudhury, 2004, but differs by having deeply lobated testes and cirrus-sac extending posteriorly to seminal receptacle level. Auriculostoma lobata n. sp. can be readily distinguished from all the other congeners by the combination of the following characters: testes located in tandem, testes deeply lobated, and larger body size. A phylogenetic analysis using 28S rDNA sequences along with those available for other allocreadiid trematodes, revealed that the new species is a sister taxon of A. astyanace, a species described from the banded astyanax, Astyanax fasciatus (Cuvier) in Nicaragua. Auriculostoma totonacapanensis Razo-Mendivil, Mendoza-Garfias, Pérez-Ponce de León & Rubio-Godoy, 2014 from the Mexican tetra, Astyanax mexicanus (De Filippi) in Mexico is the sister taxon of A. astyanace plus the new species. Genetic divergence levels for the 28S rDNA and ITS2 were estimated among the Middle-American species of Auriculostoma infecting characiforms. The validity of the new species is then established by reliable morphological differences, its host association to bryconids (Brycon guatemalensis Regan), restricted geographical distribution (Usumacinta and Lacantun River basins), and genetic divergence levels, albeit relatively low. A morphometric comparison between the new species and the other seven congeneric species was undertaken and, in addition, a taxonomic key to identify the species contained in the genus Auriculostoma, widely distributed across the Americas, is provided.